Kekerasan terhadap Anak Remaja yang Dikucilkan oleh Keluarganya dalam Novel Dear J - Sari, Putri Apika; Arifin, Berlian Putri; Ramadhan, Syahrul (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2024)
The purpose of this study is to describe and analyze the forms, causes, and consequences of violence experienced by a boy character in the novel Dear J by L. Lullaby. In this study using a qualitative approach with descriptive methods. Data sources used as objects in this study are words, sentences, and dialogues. Documentation techniques are used for data collection in this study. The documentation technique itself is a technique that seeks information or data and learns about things or variables in the form of notes, books and previous journals that support this research. This study produced results from the discussion, namely (1) the forms of violence experienced by victims were physical violence and psychological (mental) violence. (2) The causes of physical violence and psychological (mental) violence experienced by victims are due to factors in the victim's and the mother's past related to their birth. The victim was born with limitations unable to speak or is mute besides that this character is a child from a relationship outside of marriage. That is what causes both his family and friends to hate the boy character. (3) The consequences of violent behavior are damage to family relationships, loss of children's self-confidence, can cause physical and psychological injuries, and violence can also cause children to lose their right to freedom. In this way it can be concluded that the occurrence of repeated violence against the male character carried out by his family and friends results in long-term suffering and misery, and The character of the male character cannot accept it both physically and mentally